Combating incumbency advantage of network effects: The role of entrant's decisions and consumer preferences. Issue 1 (March 2019) - Gupta, Agam; Mateen, Arqum; Sharma, Divya; Sarkar, Uttam K.; Cheruvil Thomas, Vinu
This article studies the competitive dynamics between an incumbent and a late entrant in a market governed by network effects. Classifying markets based on decision criterion used by majority of consumers in a market, an analytical model for the likelihood of incumbent displacement in these markets is developed and corroborated using simulations. Using product quality offered and product price charged by the entrant as managerial levers, the impact of managerial decision-making on the expected market share of the entrant is discussed. Efficacy of seeding and delayed entry by the entrant in an attempt to perfect its product is also examined.